2020
DOI: 10.3390/su12031249
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation and Competition Impact Environmental Action: An Experimental Study in Social Dilemmas

Abstract: Previous research about social dilemmas has identified cooperation as a possible underlying facilitator of proenvironmental behavior. However, there has been no discussion about how manipulating cooperation and competition could influence environmental action experimentally. The current study filled this gap in previous literature by manipulating cooperation and competition in a group of 155 participants and comparing their respective environmental actions. Participants were randomly placed into one of three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…In fact, generative concern in relation to environmental issues was first conceptualized as an intrinsic meaning to preserve the natural environment for future generations [ 17 , 18 ]. Several recent studies have found that environmental activists tended to express generativity and cooperativeness as an intrinsic motive to act pro-environmentally in comparison to non-environmental activists [ 12 , 19 ]. Individuals who were experimentally primed to be generative were more likely to donate and donated more of their earnings to an environmental agency as compared to people in the control group [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, generative concern in relation to environmental issues was first conceptualized as an intrinsic meaning to preserve the natural environment for future generations [ 17 , 18 ]. Several recent studies have found that environmental activists tended to express generativity and cooperativeness as an intrinsic motive to act pro-environmentally in comparison to non-environmental activists [ 12 , 19 ]. Individuals who were experimentally primed to be generative were more likely to donate and donated more of their earnings to an environmental agency as compared to people in the control group [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neaman, Otto, and Vinokur [ 10 ] further demonstrated that prosocial and pro-environmental behaviors are the “two facets of a broader trait”, which, in turn, strengthen the environmental educational programs. Other studies also found a similar pattern between prosocial orientation and specific environmental decision-making such as commuting behaviors [ 11 ], environmental political behaviors [ 12 ], and daily participatory environmental actions [ 13 ].…”
Section: Introductionmentioning
confidence: 61%
“…They found no difference between the experimental condition and the control condition regarding participants’ behavioral choices. Similar, Curtin and Jia [ 13 ] primed participants using autobiographical memories, but they did not find the group differences on self-reported pro-environmental actions. These studies suggest that priming social value orientations cannot influence people’s conservational behaviors due to a methodological issue (e.g., priming).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations